CARGA DE VENTO SOBRE COLETORES SOLARES EM HABITAÇÕES TÉRREAS DE INTERESSE SOCIAL VIA SIMULAÇÃO CFD - Ara, Paulo; Sowmy, Daniel; Prado, Racine; Kurokawa, Fernando (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In the context of growing use of renewable energy sources, solar water heating has been a prominent alternative. In Brazil, solar thermal is increasingly being used for many purposes, as well as in social housing. In all cases, solar collector must meet requirements specified by national standards. One of them is the glass cover resistance to mechanical load. The national standard requires that the collector cover resist to compression load of 1 kPa, proved by laboratory tests. This work aims to analyze wind loads on solar collectors installed on social housing inclined roofs and compare them with the 1kPa normative requirement. For this, CFD simulations were performed to determine the pressure coefficients on roof integrated solar collector considering usual typologies of social housing in Brazil and thus to calculate the actual positive pressures upon the collectors. The results showed that, for the studied wind directions, there is predominance of suction at the collector surface instead of compression. The most critical situations of compression occur for roofs with high slope, with inclinations higher than 30°, approximately. The conclusion is that 1kPa Brazilian requirement represents, in worst situations, nearly 3 times the actual wind pressures upon the collectors for the applications studied.